Blast-induced damage and secondary fragments of reinforced concrete slab and wall under close-in explosions - Wang, Zitong (Curtin University, 2024)
This thesis conducts the analysis and assessment of the blast-induced damage, and secondary fragments of RC slabs and walls subjected to close-in TNT explosions. The outputs derived from this thesis can provide references and guidance for the prediction of resultant damage and secondary fragments as well as safety distances required for human protection in the surrounding vicinity.